Pedagogical strategies for drum learning: A qualitative study on fun and discipline for elementary students - Piter Sembiring; Imelda Aprillia Sitanggang; Clarisa Jesika Korina Tiurmauli Hutapea (Universitas Papua, 2025)
This study examines the balance between fun and discipline in drumming lessons for primary school students at Favore Music, a non-formal music education institution. The aim of the study is to explore effective pedagogical strategies that can increase students' motivation, engagement, and mastery of skills through a combination of fun activities and technical discipline. Using a qualitative approach, data were collected through participatory observation, in-depth interviews, and documentation. The findings show that the integration of fun activities, such as rudiment rhythm games and drum cover challenges, can increase student engagement while maintaining a focus on technical aspects. The role of the teacher as both instructor and facilitator is crucial in providing interactive feedback and structured challenges to encourage skill development. The results show that students who engage in fun activities show increased motivation and perseverance, which leads to improved technical ability. This study concludes that a balanced approach between fun and discipline is essential for effective music education, which not only develops musical skills, but also motivates and builds long-term resilience in students.